Modifications adaptive to an aquatic habitat in the Coleoptera - Gahan, Arthur B. (My University, 1903)
Introduction: Those representatives of the Coleoptera characterized by an aquatic habit show many interesting and remarkable variations from other beetles in their structure fitting them for such a life. Most of the various parts of the insect body are involved to a greater or lest extent in these modifications, but the most notable digressions from the structure of the terrestrial beetle are found in the shape of the body, in the manner of breathing, and in the structure of the legs. Adaptations are also noticeable in the length, shape, and position of the antennae, in the number and position of the eyes, and occasionally in the sculpturing of the elytra. In an article of the length of this it would be impossible to treat all of the various coleopterous insects inhabiting the water even were it possible to obtain specimens for such a treatment. Hence I have decided to limit the subject to a discussion and illustration of the principal adaptations found in the three great families Dytiscidae, Gyrinidae, and Hydrophilidae. Since the individual species of each family do not differ greatly from one another, it will be necessary to use but a single species as indicative of the adaptations found in that family. As the well-known family Dytiscidae is generally recognized as first in the order of development, it will properly be taken up first. THE DYTISCIDAE. Preliminary to taking up the discussion of the adaptations of Dytiscidae to an aquatic life, it may be well to state briefly what their habits are. The entire family is composed of rapacious diving beetles that obtain their food by the destruction of smaller water insects and occasionally young fishes. The larval and pupa stages are passed in the water and upon moist earth respectively. The imago frequents ponds and pools of stagnant water in which there is a growth of water plants .Most of its time is spent beneath the water but it must occasionally rise to the surface for fresh air and often at nights it comes out and flies to a new pool or pond.
Citation: Gahan, Arthur B. Modifications adaptive to an aquatic habitat in the Coleoptera. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Dytiscidae; Cybister; Hydrophilidae; Theses